ESTETIKA IDEOLOGI MEDIA ABOVE THE LINE PRODUK SUPLEMEN MEREK “MADURASA” PT. AIR MANCUR - Pujiyanto Pujiyanto (Fakultas Sastra Universitas Negeri Malang, 2013)
This study aims to determine the textual and contextual aesthetic ideology on above the line “Madurasa”. This research applied a case study using qualitative descriptive design drawing or writing on the ads published in newspapers, tabloids, and magazines. Data was obtained from observation, interviews, and documentation, while the analysis using the theory of ideology “hegemony” Antonio Gramsci. The result shows that the advertising media are ideological strategy of “hegemony” through the elements of typography, images, colors, logos, and lay out